Склепы могильника Совхоз № 10 (Севастопольский): проблемы этноса и хронологии - Высотская, Т.Н. (Материалы по археологии, истории и этнографии Таврии, 1998)
Могильник "Совхоз N° 10" один из интереснейших памятников Северного Причерноморья первой половины первого тысячелетия нашей эры. Он расположен в Инкерманской долине на правом берегу р.Черной на территории совхоза № 10 (откуда его название), к юго-востоку от подножья Сахарной головки, на водоразделе двух балок. A group of the latest burial constructions of "Sovkhoz 10" cemetery - vaults similar to the ones in the Northern Caucasus is considered in this article. All the discovered vaults were plundered in ancient times. Nevertheless, their inventory: red-lacquered and modelled pottery, glass vessels, tools, buckles, mirrors, a brooch (fibula), fragments of amphoras, an earring, beads - enables — us to date the vaults by the the end of the 4th - the beginning of the 5th centuries A.D. They belong to the Alanic ethnos. The reasons why the life in this settlement stopped are not clear.